PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE FORMASI REGU TEMBAK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN LUBUK BUAYA KOTA PADANG - Danil, Haryadi - (STKIP PGRI Sumbar, 2014)
The research has the background, that is because of the students who have lessresponsibility in doing the exercise which is given by the teacher and the studentâsmathematical concept comprehension is still low. The purpose of this research isto know Does Firing Line Type of Active Strategy influence toward StudentâsMathematical Concept Comprehension at the Eight Grade Students of MTsNLubuk Buaya City. The design of this research is the experimental research, withthe research plans are pre test and post test. The instrument used in this researchis the mathematical concept comprehension test, these are pre test and post test.Form tes the used form is breakdown of with validity by teacher. Techniqueanalyse data the used is test t. Pursuant to result of hypothesis test obtained byvalue. Based on the hypothesis test result, itâs gotten the ð¡ððð¢ðð¡ = 26.45 andð¡ð¡ðððð = 1.68 with ð¼ = 0.05. Becoming hypothesis accepted because ð¡ððð¢ðð¡ >ð¡ð¡ðððð and concluded that there are influence Active Strategy Study The FiringLine to understanding of mathematical concept class student VIII MTSN LubukBuaya City.